Muhammad dan Orisinalitas Al-Quran dalam Pandangan Abraham Geiger - Muhamad Mahfudin (MAGHZA, 2021)
Among the interest in the study of Muhammad and the Quran was born from the Orientalists. Including the Orientalists who were very influential on this study was Abraham Geiger. From this research, it is found that Geiger has a view that tends to be contrary to that of Muslim scholars in general. Where Geiger views that Muhammad was someone who had tried to bring up the Quran because it was influenced by the Jewish culture that already existed in the Arab region at that time. Geigers opinion is based on several facts that he put forward, which include: When Muhammad carried out his mission in Medina, Muhammad was dealing with Jews who had long had a strong influence on the local community and Muhammad had close relations with Jews. in the area. This fact is then reinforced by Geigers findings in the Qur'an which are indicated to be taken from the Jewish tradition, such as the discovery of 14 vocabulary words of the Koran which tend to be the same as Jewish dogma, the discovery of doctrinal concepts that indicate the adaptation of the Qur'an from the Jews. and the stories in the Koran that tend to be in line with Jewish teachings.